ONLINE BASED PARKING BUSINESS PLANNING WITH PARTNERSHIP CONCEPTSIN BANDUNG CITY (International Journal of Psychosocial Rehabilitation, 2020)
The birth of Bukalapak is the answer to problems experienced by people when they want to shop but cannot or do not have time to directly buy the desired item. Thus, Bukalapak was present to answer the problem. Same thing with Gojek. When people, especially in urban areas, have begun to struggle to find practical transportation to reach their destinations, Gojek is here to give them convenience and security. If a short conclusion is drawn from the concise discussion, it can be concluded that the problem is a business opportunity when we can find or provide a solution. The owner of a place like the mall manager who formed a partnership with "Parkiran" will certainly get many benefits. As they no longer need to pay a third party as the parking manager and also, the safety and comfort equipment that is in their parking lot will be equipped directly by "Parking". "Parking lots" also provide an opportunity for residents around the crowd to register their vacant yard land as an alternative parking area that can be used by "Parking" users. The concept of business application from the application "Parking" can certainly be spelled out simply by using the concept of partnership with the manager of the mall or other public places as well as partnering also with residents who want to rent out land in his yard for parking.